YEONG-HYE’S VEGETARIAN AFFECTS TO SOCIAL LIFE IN HANKANG “THE VEGETARIAN”: Rejection, Deviant behaviour, and Negative reaction(stigma) - Faisol Amin; Ika Trisnantasari; Novi Sriwulandari (Fakultas Sastra Universitas Gresik, 2023)
Hankang the vegetarian novel tells the woman named Yeong-hye who decided to be vegetarian after having nightmare, being vegetarian Yeong-hye got negative reaction(stigma) from her family and society. This study was descriptive qualitative in nature which used the data from whole novel of the vegetarian and to support the study, the researcher used theory of vegetarian in social cultural context and theory of vegetarian effect in society. The result of this study, the researcher finds that to be vegetarian cannot accept in Korean society because of collectivism influence, which collectivism hold the value of interdependence that prioritize the goal of group so that vegetarian was consider as a deviant behaviour that can disturb harmony in group and discordance with non vegetarian.